2021
DOI: 10.1101/2021.09.15.460511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synaptotagmin-1-dependent phasic axonal dopamine release is dispensable for basic motor behaviors in mice

Abstract: Midbrain dopamine (DA) neurons, a population of cells that are critical for motor control, motivated behaviors and cognition, release DA via an exocytotic mechanism from both their axonal terminals and their somatodendritic (STD) compartment. In Parkinson's disease (PD), it is striking that motor dysfunctions only become apparent after extensive loss of DA innervation. Although it has been hypothesized that this resilience is due to the ability of many motor behaviors to be sustained through a basal tone of DA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…Of these, Syt1 and Syt7 have Ca 21 -binding C2 domains, with Syt1 having low Ca 21 affinity and Syt7 having high Ca 21 affinity (Sugita et al, 2002;Pinheiro et al, 2016). Previous work has shown that Syt1 mediates fast, synchronous transmitter release (Geppert et al, 1994;Xu et al, 2007), including axonal DA release in dorsal striatum (Banerjee et al, 2020;Delignat-Lavaud et al, 2021). High-affinity Syt7 also contributes to asynchronous exocytotic release in neurons and secretory cells (Gustavsson et al, 2009;Jackman et al, 2016;Chen et al, 2017;Luo and Südhof, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, Syt1 and Syt7 have Ca 21 -binding C2 domains, with Syt1 having low Ca 21 affinity and Syt7 having high Ca 21 affinity (Sugita et al, 2002;Pinheiro et al, 2016). Previous work has shown that Syt1 mediates fast, synchronous transmitter release (Geppert et al, 1994;Xu et al, 2007), including axonal DA release in dorsal striatum (Banerjee et al, 2020;Delignat-Lavaud et al, 2021). High-affinity Syt7 also contributes to asynchronous exocytotic release in neurons and secretory cells (Gustavsson et al, 2009;Jackman et al, 2016;Chen et al, 2017;Luo and Südhof, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Because Syt1 is the main calcium sensor of axonal DA release [ 3 , 42 , 43 ], and Syt4 and Syt7 were previously suggested to be critical for STD DA release based on in vitro experiments [ 3 ], we next evaluated the presence and subcellular localization of these Syt isoforms in DA neurons in vivo in the mouse brain.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore estimated the density of potential neurotransmitter release sites (varicosities) along the axonal domains of these projecting neurons (Figure 7A, 7B). Following 10 DIV, we segmented probable varicosities, identified them based on morphology and dimensions, and evaluated the presence of synaptotagmin1 (Syt1), a calcium sensor of exocytosis that is critical for neurotransmitter release in DA neurons (Banerjee et al, 2020;Delignat-Lavaud et al, 2021;Mendez et al, 2011), as an index of release-competent terminals. Strikingly, we find that vulnerable neurons have a significantly higher proportion of varicosities that are positive for Syt1 (Figure 8A, 8B, Extended Tables 8-1), suggesting that these neurons have a higher proportion of active neurotransmitter release sites.…”
Section: Resultsmentioning
confidence: 99%
“…7 A , B ). Following 10 DIV, we segmented probable varicosities, identified them based on morphology and dimensions, and evaluated the presence of Syt-1, a calcium sensor of exocytosis that is critical for neurotransmitter release in DA neurons ( Mendez et al, 2011 ; Banerjee et al, 2020 ; Delignat-Lavaud et al, 2021 ), as an index of release-competent terminals. Strikingly, we find that vulnerable neurons have a significantly higher proportion of varicosities that are positive for Syt-1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%